INCREASING THE ACTIVITY AND OUTCOMES OF SCIENCE LEARNING THROUGH THE IMPLEMENTATION OF THE DISCOVERY LEARNING MODEL IN STUDENT X AT SMK AL KHAIRIYAH CIOMAS - Hermawan, Hermawan; Saefurahman, Asep (Transpublika Publisher, 2024)
This action research aims to increase student activity and learning outcomes through the application of discovery learning models in class X students at SMK Al Khairiyah Ciomas. The subjects of this research were 30 students in class X. What is used is classroom action research with the Kemmis and Mc model. Taggart. Each cycle is carried out with stages: planning, action implementation, observation and reflection. The results of the analysis of descriptive data show that in cycle I student learning outcomes have not yet reached the minimum completeness criteria (KKM) applied because they have only achieved an average score of 67.60 from a KKM score of 75, and an absorption capacity of 50% which means that 15 students have fulfilled the KKM and 15 students have not reached KKM. This is due to the activeness of students in learning 61.60 while the ability of teachers in learning has only reached 75%. From these results it is necessary to proceed to cycle II. And as for the results of the actions in cycle II that the average student learning outcomes were 76.20, which meant that they had reached the KKM and the absorption was 76.67%, which meant that 23 students had exceeded the KKM. While the ability of teachers by 85%. Because this research had reached KKM, this research was not continued in the next cycle. The results of the study concluded that the application of the discovery learning model can increase the activity and learning outcomes of science.